Bank competition and collateral: theory and evidence - Christa Hainz; Laurent Weill; Christophe J. Godlewski (Bank of Finland, 2008)
We investigate the impact of bank competition on the use of collateral in loan contracts. We develop a theoretical model incorporating information asymmetries in a spatial competition framework where banks choose between screening the borrower and asking for collateral. We show that presence of collateral is more likely when bank competition is low. We then test this prediction empirically on a sample of bank loans from 70 countries. We estimate logit models where the presence of collateral is regressed on bank competition, measured by the Lerner index. Our empirical tests corroborate the theoretical predictions that bank competition reduces the use of collateral. These findings survive several robustness checks.
URN:NBN:fi:bof-20140807141
Keywords: 330